Características agronômicas de híbridos de milho para produção de silagem cultivados em quatro estados brasileiros - Bastos, Márcio de Souza (2019)
Identifying the traits of corn hybrids used for silage making under commercial conditions is crucial for milk and beef industries. The aim of this study was to characterize corn fields and hybrids grown in four Brazilian states. Seventy-four corn fields (48 and 26 for the first and second growing seasons, respectively) were visited for 2-yr. Descriptive statistics was used to characterize corn fields and hybrids using SAS software. The Ward’s hierarchical clustering analysis was carried out to group fields and a principal component analysis was performed to identify traits associated with dry matter yield using Statistica software. Yield varied from 16 to 43 ton DM/ha and from 13 to 23 ton DM/ha for the first and second growing season, respectively. Grain yield and grain proportion were greater for fields grown during the first season. Conversely, stover yield and stover proportion were greater for fields grown during the second season. Ear with more kernels and longer kernels determined greater grain yield. Taller plants with thicker stalk were related with greater stover yield. Thus, forage yield was associated with number of kernels per ear, kernel length, plant height, and stalk thickness. Overall, hybrids demonstrated great potential to yield corn forage, especially those grown during the first growing season.